Are Clay Minerals the Primary Control on the Oceanic Rare Earth Element Budget? - Abbott, April N.; Löhr, Stefan; Trethewy, Megan (Frontiers in Marine Science, 2019)
The rare earth elements (REEs) are an important tool for understanding biogeochemical cycling and sedimentary processes in the global ocean. However, ambiguities in the marine REE budgets, including questions around the dominant source of REEs to the ocean, hinder the application of this tool. A bottom-up model for REE release into the ocean has recently been proposed, driven by early diagenetic processes such as sediment dissolution, with potentially significant implications for the interpretation of marine REE and Nd isotope paleo-records. Here, our goal is to identify the phase or phases that interact with the pore fluids to drive such a benthic flux. We use new pore water REE, microbeam imaging and mineralogical data in combination with published pore water REE data to evaluate potential sedimentary REE host phases. Mineralogical and direct imaging observations suggest that authigenic Fe or Mn oxyhydroxides, which are widely considered a dominant REE host phase, are not sufficiently abundant sediment components to account for the high Nd concentrations recovered in reductive leaches, and are unlikely to be the primary source of pore water REEs. Pore water REE signatures similar to river sourced clays indicate a detrital clay dissolution source, while the spread in heavy to light REE enrichment in pore fluids and bottom waters relative to this clay source is best explained by fractionation during authigenic clay uptake of REEs. We therefore conclude that clay mineral dissolution and authigenesis are likely the primary influences on the REE cycling near the seafloor. We propose that the balance between dissolution and authigenesis controls the concentration, ratio of heavy and light REE abundances, and the isotopic composition of the pore waters. We discuss the implications of this hypothesis on an oceanic REE budget controlled by a benthic flux from a sedimentary REE source, and the use of authigenic neodymium isotopes as a paleoproxy for shifts in ocean circulation.